2018
DOI: 10.1136/thoraxjnl-2017-211440
|View full text |Cite
|
Sign up to set email alerts
|

Growth/differentiation factor 15 causes TGFβ-activated kinase 1-dependent muscle atrophy in pulmonary arterial hypertension

Abstract: IntroductionSkeletal muscle dysfunction is a clinically important complication of pulmonary arterial hypertension (PAH). Growth/differentiation factor 15 (GDF-15), a prognostic marker in PAH, has been associated with muscle loss in other conditions. We aimed to define the associations of GDF-15 and muscle wasting in PAH, to assess its utility as a biomarker of muscle loss and to investigate its downstream signalling pathway as a therapeutic target.MethodsGDF-15 levels and measures of muscle size and strength w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Recent data from animal models showed that GDF15 is able to induce muscle fiber apoptosis (12,13), but also the ablation of GDF15 resulted in an amplified skeletal muscle post exercise stress response, with a bigger increase of markers of muscle stress (Atf3, Atf6, and Xbp1s) (14). In humans, circulating GDF15 levels are significantly higher in subjects with sarcopenia or muscle atrophy (15)(16)(17) with respect to healthy subjects of comparable age. Recent studies demonstrate that GDF15 levels are negatively correlated with skeletal muscle mass index, handgrip strength, muscle cross-sectional area and thickness (15,18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from animal models showed that GDF15 is able to induce muscle fiber apoptosis (12,13), but also the ablation of GDF15 resulted in an amplified skeletal muscle post exercise stress response, with a bigger increase of markers of muscle stress (Atf3, Atf6, and Xbp1s) (14). In humans, circulating GDF15 levels are significantly higher in subjects with sarcopenia or muscle atrophy (15)(16)(17) with respect to healthy subjects of comparable age. Recent studies demonstrate that GDF15 levels are negatively correlated with skeletal muscle mass index, handgrip strength, muscle cross-sectional area and thickness (15,18).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, GDF-15, a protein of the TGF-β family, has been shown to be associated with muscle atrophy in some chronic diseases. It has also been proven to be an ideal biomarker for muscle and weight loss in patients with pulmonary hypertension [13]. GDF-15 is gradually receiving more attention in the field of critical care due to its possible involvement in the pathogenesis of ICU-AW [14].…”
Section: Discussionmentioning
confidence: 99%
“…Promotes proliferation and differentiation in fetal lung development (19) Maternal serum levels increase throughout during pregnancy (12) High serum levels in term neonates that decline postnatally (20) Upregulated in neonatal mice exposed to hyperoxia in vivo (21) Upregulated in pulmonary epithelial and endothelial cells exposed to hyperoxia (22) GDF15 loss leads to decreased cell viability and increased oxidative stress (23) Chronic Obstructive Pulmonary Disease (COPD) Higher serum levels are associated with increased morbidity and mortality (4,24) Mediates smoking-induced inflammation and cellular senescence (25)(26)(27) Promotes mucin production in ciliated epithelial cells (28) Exacerbates lung inflammation secondary to infection (29) Contributes to cachexia: GFRAL mediated signaling, induces lipolysis and promotes muscle wasting (30)(31)(32)(33) Pulmonary Hypertension (PH) Associated with prognosis and response to therapy (34)(35)(36) Levels increased in pediatric PH related to congenital heart disease (37) Associated with increase in right atrial and pulmonary capillary wedge pressure (34) Induces muscle atrophy that is reversed by TAK1 inhibitor (38) Promotes angiogenesis and hinders endothelial cell apoptosis (39,40) Lung Fibrosis Associated with disease severity (41) Associated with higher odds of interstitial lung abnormality (42) Activates fibroblasts and M2 macrophages (40) Prevents the activation of fibroblasts during lung remodeling (43) FIGURE 1 | Cellular senescence and lung disease across the lifespan: role of GDF15.…”
Section: Age/condition Role Of Gdf15 Referencesmentioning
confidence: 99%